Identification of Suitable Sites for Solid Waste Disposal using GIS Multi-criteria Analysis in Peshawar, Pakistan: Identification of Suitable Sites for Solid Waste Disposal - Samiullah,; Atta-ur-Rahman,; Shah, S. Akhtar Ali; Khan, Zahid; Nawaz, Shah (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2016)
In this paper an effort has been made to identify suitable sites for safe disposal of municipal and other solid waste generated in Peshawar City District. Using GIS and Remote Sensing for identification of landfill site is more economical and effective than traditional techniques. Selection of suitable site depends on a number of factors to ensure environment friendly disposal of solid waste. For analysis and identification of suitable site for safe disposal in Peshawar city district, SPOT satellite image of 2010 and Topographic sheets have been used as a base map. Primary and secondary data were collected from various sources. Using multicriteria analysis in ArcGIS 9.3, surfaces were generated for all the selected parameters by applying spatial analysis tools. Weighted parametric values were assigned to all the layers using some of the Environmental Protection Agency standards parameters for selection of landfill site. The sites were selected having minimum environmental consequences. Based on the selected parameters including distances from residential areas, airport, water bodies, distance to spine roads, water table, land values, slope stability and land use pattern were used. As a result, the entire Peshawar city district was divided into three regions of least suitable, moderately suitable and most suitable landfill sites. The most suitable sites were located largely in southern parts of the city district where weight according to site suitability was the highest.